Individual patient meta-analysis of single-dose rofecoxib in postoperative pain - Edwards, Jayne E (BioMed Central, 2004)
BACKGROUND: Individual patient meta-analysis to determine the analgesic efficacy and adverse effects of single-dose rofecoxib in acute postoperative pain. METHODS: Individual patient information was available from 14 trials; 13 in dental and one in postsurgical pain. For each patient the percentage of maximum possible pain relief (%maxTOTPAR) was determined at different time points. The proportion of patients with at least 50% maxTOTPAR, and number-needed-to-treat (NNT) for at least 50% maxTOTPAR, were then calculated, with time when 50% of patients had remedicated (TTR(50)) and number-needed-to-harm (NNH) for adverse effects. RESULTS: In dental pain, for rofecoxib 50 mg (1330 patients) compared with placebo (570 patients) the NNT was 1.9 (95% confidence interval 1.8 to 2.1) for six hours, 2.0 (1.8 to 2.1) at eight, 2.4 (2.2 to 2.6) at 12, and 2.8 (2.5 to 3.1) at 24 hours. The TTR(50 )was 15.5 hours. Adverse effects were uncommon, though post-extraction alveolitis (dry socket) occurred more often with rofecoxib 50 mg than with placebo, NNH 24 (14 to 80). For postsurgical pain in one trial (163 patients), the NNT for rofecoxib 50 mg for six hours was 3.9 (2.6 to 7.8), the TTR(50 )was 5.8 hours, and multiple-dose adverse effects over five days occurred at similar rates with rofecoxib 50 mg and placebo. CONCLUSIONS: Single-dose rofecoxib 50 mg is an effective treatment with long-lasting analgesia and few adverse effects in dental pain. More information is required to confirm efficacy in postsurgical pain.